Study of antibiotic susceptibility of uropathogenic germs and epidemiology in patients at the Ignace Deen National Hospital in Conakry (Republic of Guinea) - Camara, Taliby Dos; Makanera, Abdoulaye; Camara, Bintou; Camara, Mory (The Asia Journal of Applied Microbiology, 2023)
Out of 228 urines analysed, the prevalence was 85%. Married people are the most exposed, with 78%. Households (30%), administrative staff (19%) and patients from the commune of Kaloum (35%) were the most represented. 58% were male, with a sex ratio (male/female) of 0.73. The 51 and over age group was the most affected with 32%, followed by the 21-30 age group with 19% and the 31-40 age group with 16%. The age groups least represented were 11-20 and 0-10 with 5% and 6% respectively. Married people are the most affected, with 82%, compared with 18% of single people. The married/single ratio is 4.5. Housewives are the most represented with 15%, followed by sales staff with 18% and pupils/students with 13%. Patients from the Urology department accounted for 45%, followed by Gynaecology with 21%, Rheumatology with 12%, and patients from elsewhere accounted for 10%. Patients from the commune of Kaloum were the most represented with 36%, followed by patients from outside Conakry with 20% and Matam with 19%. 61% of the urine was clear, 33% turbid and 6% haematic. 15% of urine was germ-free, 63% contained gram-negative bacilli and 37% gram-positive cocci. Leukocyturia was significant in 86% of cases. Epithelial cells were present in 6%, haematuria in 3%, yeast in 3% and oxalate crystals in 2%. The germ Escherichia coli was the most incriminated in 40% followed by Staphyloccus aureus with 32%, Klebsiella pneumoniae with 8%, Pseudomonas aeruginosae with 5%, Acinetobacter baumannii with 3% and Staphylococcus haemolyticus with 2% and the other germs were 1%. Antibiotics such as amikacin were effective in 63%, Nitrofurantoine in 79% and Imipenem in 76%.